Regional and institutional trends in assessment for academic promotion - Lim, B. H.; D’Ippoliti, C.; Dominik, M.; Hernández-Mondragón, A. C.; Vermeir, K.; Chong, K. K.; Hussein, H.; Morales-Salgado, V. S.; Cloete, K. J.; Kimengsi, J. N.; Balboa, L.; Mondello, S.; et al. (Nature (London), 2025)
The assessment of research performance is widely seen as a vital tool in upholding the highest standards of quality, with selection and competition believed to drive progress. Academic institutions need to take critical decisions on hiring and promotion, while facing external pressure by also being subject to research assessment 1 , 2 , 3 – 4 . Here we present an outlook on research assessment for career progression with specific focus on promotion to full professorship, based on 314 policies from 190 academic institutions and 218 policies from 58 government agencies, covering 32 countries in the Global North and 89 countries in the Global South. We investigated how frequently various promotion criteria are mentioned and carried out a statistical analysis to infer commonalities and differences across policies. Although quantitative methods of assessment remain popular, in agreement with what is found in more geographically restricted studies 5 , 6 , 7 , 8 – 9 , they are not omnipresent. We find differences between the Global North and the Global South as well as between institutional and national policies, but less so between disciplines. A preference for bibliometric indicators is more marked in upper-middle-income countries. Although we see some variation, many promotion policies are based on the assumption of specific career paths that become normative rather than embracing diversity. In turn, this restricts opportunities for researchers. These results challenge current practice and have strategic implications for researchers, research managers and national governments. Analysis of policies for promotion criteria to full professor from academic institutions and government agencies worldwide reveals considerable variation in assessment practices, particularly between the Global North and South.